2018
DOI: 10.1016/j.appet.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Eating with others and meal location are differentially associated with nutrient intake by sex: The Diabetes Study of Northern California (DISTANCE)

Abstract: Though eating with others is often a social behavior, relationships between social contexts of eating and nutrient intake have been underexplored. This study evaluates how social aspects of eating - frequencies of eating meals with others, meals prepared at home, and meals outside the home - are associated with nutrient intake. Because diet improvement can reduce complications of diabetes mellitus, we surveyed a multi-ethnic cohort of persons with type 2 diabetes (n = 770) about social aspects of diet (based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
2
17
1
Order By: Relevance
“…Among the identified papers on commensality assessment, 51 papers were categorized as qualitative. These were put into subcategories, such as qualitative interviews ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and ethnological studies ( Table 3 ) [ 42 , 43 , 44 , 45 , 46 , 47 ], log book plus interview ( Table 4 ) [ 48 , 49 , 50 , 51 ] case studies ( Table 5 ) [ 52 , 53 ] and diverse methods ( Table 6 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified papers on commensality assessment, 51 papers were categorized as qualitative. These were put into subcategories, such as qualitative interviews ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and ethnological studies ( Table 3 ) [ 42 , 43 , 44 , 45 , 46 , 47 ], log book plus interview ( Table 4 ) [ 48 , 49 , 50 , 51 ] case studies ( Table 5 ) [ 52 , 53 ] and diverse methods ( Table 6 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , …”
Section: Resultsmentioning
confidence: 99%
“…A great deal of the identified research is focused on health and nutrition, aiming to investigate the importance of commensality for health and wellbeing [ 12 , 13 , 14 , 15 , 16 , 18 , 20 , 22 , 24 , 26 , 30 , 33 , 39 , 46 , 58 , 65 , 67 , 69 ]. This means that data on health and health related behaviors, living conditions and sociodemographic data, need to accompany the data on commensality.…”
Section: Discussionmentioning
confidence: 99%
“…The Organization dimension is related to the preparation and consumption of meals at home, as indicated by the inclusion of the expression ‘in my home’ in different items. The influence of the domestic environment on eating habits has been corroborated in the literature; for example, the study by Pachucki et al ( 51 ) found a direct association between diet quality and meals prepared and consumed at home by men and inversely between meals consumed outside of home by women in a sample of diabetic individuals. The authors discuss the gender difference in the light of persistent discrepancies in household task overload.…”
Section: Discussionmentioning
confidence: 77%
“…The organization dimension is related to the preparation and consumption of meals at home, as indicated by the inclusion of the expression "in my home" in different items. The influence of the domestic environment on eating habits has been corroborated in the literature; for example, the study by Pachucki et al (51) found a direct association between diet quality and meals prepared and consumed at home by men and inversely between meals consumed outside of home by women in a sample of diabetic individuals. The authors discuss the gender difference in light of persistent discrepancies in household task overload.…”
Section: Discussionmentioning
confidence: 76%
“…This study is a methodological study based on knowledge of psychometry, which is a science that studies the measurement of non-directly observable phenomena (i.e., psychological phenomena) that can be characterized using a set of other attributes (19) . This feature can be useful for the construction of instruments for diet measurement in relation to the adoption of paradigms that consider diet a result of complex 51 relationships among different determinants. A self-administered scale is proposed for the Brazilian adult population (18 to 60 years old).…”
Section: Methodsmentioning
confidence: 99%